Anorexia nervosa may not depend on the body mass index and may occur in patients with normal weight, overweight or obese - Sak, Lesia (Psychosomatic Medicine and General Practice, 2019)
According to a new study by researchers from UCSF, adolescents and young people with anorexia nervosa (AN), whose weight is within normal, overweight or obese, have cardiovascular and other health complications, like AN patients with low body mass index (BMI).